CONTRIBUIÇÕES DA METODOLOGIA BASEADA EM PROBLEMAS PARA O ENSINO DE FISIOLOGIA HUMANA EM CURSOS NA ÁREA DE SAÚDE - Souza, Clauberto Medeiros de (2019)
With the changes that occur every day in postmodern society, the need has been observed by the Higher Education Institutions to incorporate new methodologies into teaching practice. As a possibility of a contextualized teaching and at the same time challenging for the critical formation of the individual, the Problem Based Learning (PBL) has been highlighted, mainly because it puts the student in the role of protagonist for the acquisition of new knowledge. The PBL provides students with numerous teaching possibilities, such as collective work, respect for colleagues, the search for possible solutions, intragroup and intergroup discussion, intermediation between teacher (facilitator) and student, in order to bring these attitudes closer to the world. and the possibility of resolving issues already experienced during graduation in the future. The objective of this research was to verify to what extent the PBL methodology can promote the learning of the Endocrine Glandular System Physiology theme with the students of a course in the health area. The research was characterized by presenting a qualitative approach, of applied and interpretative nature, with interest in knowing how the PBL methodology can benefit the student learning. This research had as its guiding principle the application of a Didactic Sequence (SD) from the perspective of PBL in a group of 33 students, enrolled in the 2nd period of the Bachelor Degree Physiotherapy course, from a private Higher Education Institution, Guairacá-PR, in the discipline of human physiology. As results it can be observed that the application of a DS from the perspective of PBL benefited the study about the understanding and fixation of the Endocrine Glandular System by the students. Comparing the results of the pretest with the posttest, it can be observed that the students were able to add new knowledge to the existing ones, pointing to meaningful learning, and also provided to those who did not present knowledge, a new perspective of teaching methodology. significant. In addition, the post-test results showed that by changing the way of learning / teaching, the student was equipped to face the challenge to seek information, building new knowledge of great importance for solving problem situations that the future health teacher may encounter.